Realizing Universal Health Coverage in East Africa: the relevance of human rights - Alicia Ely Yamin (BMC International Health and Human Rights, 2017)
Abstract Applying a robust human rights framework would change thinking and decision-making in efforts to achieve Universal Health Coverage (UHC), and advance efforts to promote women’s, children’s, and adolescents’ health in East Africa, which is a priority under the Sustainable Development Agenda. Nevertheless, there is a gap between global rhetoric of human rights and ongoing health reform efforts. This debate article seeks to fill part of that gap by setting out principles of human rights-based approaches (HRBAs), and then applying those principles to questions that countries undertaking efforts toward UHC and promoting women’s, children’s and adolescents’ health, will need to face, focusing in particular on ensuring enabling legal and policy frameworks, establishing fair financing; priority-setting processes, and meaningful oversight and accountability mechanisms. In a region where democratic institutions are notoriously weak, we argue that the explicit application of a meaningful human rights framework could enhance equity, participation and accountability, and in turn the democratic legitimacy of health reform initiatives being undertaken in the region.